Maternal Overprotection and Cost-Inflicting Retention: A Mediational Model of Machiavellian Personality Traits - Sylvia Andrian; Fivi Nurwianti (Psikostudia : Jurnal Psikologi, 2025)
Previous research indicates that maternal overprotective parenting can contribute to the development of Machiavellian traits, characterized by manipulative behavior. These traits are often found in cost-inflicting mate retention strategies, where individuals attempt to control their partners through coercion, jealousy, and emotional manipulation. This study aimed to examine whether Machiavellianism mediates the relationship between maternal overprotective parenting and cost-inflicting mate retention strategies among emerging adults in Indonesia. A total of 725 participants (aged 18-40 years, M = 28.7) who were in romantic relationships for at least six months participated in this cross-sectional study. Data were collected online using the Short Dark Tetrad (SD4), Mate Retention Inventory-Short Form (MRI-SF), and Short Egna Minnen Beträffande Uppfostran (s-EMBU). Analysis was conducted using Structural Equation Modeling (SEM). Results showed that maternal overprotective parenting positively predicted cost-inflicting strategies (β = 0.198, p < 0.001), and Machiavellianism was significantly associated with cost-inflicting behavior (β = 0.18, p < 0.001). Mediation analysis revealed that Machiavellianism partially mediated the relationship between maternal overprotective parenting and cost-inflicting behavior (β = 0.041, p = 0.001), with a total effect of β = 0.240 (p < 0.001). These findings highlight the long-term impact of overprotective parenting patterns on romantic behavior in adulthood and encourage further research on other psychological mechanisms that influence manipulative mate retention strategies.Penelitian sebelumnya menunjukkan bahwa pengasuhan overprotektif ibu dapat berkontribusi terhadap berkembangnya sifat Machiavellian, yang ditandai dengan perilaku manipulatif. Sifat ini sering ditemukan dalam strategi retensi pasangan yang bersifat cost-inflicting, di mana individu berusaha mengontrol pasangannya melalui paksaan, kecemburuan, dan manipulasi emosional. Penelitian ini bertujuan untuk menguji apakah Machiavellianisme memediasi hubungan antara pengasuhan overprotektif ibu dan strategi cost-inflicting mate retention pada dewasa awal di Indonesia. Sebanyak 725 partisipan (usia 18-40 tahun, M = 28,7) yang sedang menjalin hubungan romantis minimal enam bulan berpartisipasi dalam penelitian cross-sectional ini. Data dikumpulkan secara daring menggunakan Short Dark Tetrad (SD4), Mate Retention Inventory-Short Form (MRI-SF), dan Short Egna Minnen Beträffande Uppfostran (s-EMBU). Analisis menggunakan Structural Equation Modeling (SEM). Hasil menunjukkan bahwa pengasuhan overprotektif ibu secara positif memprediksi strategi cost-inflicting (β = 0,198, p < 0,001), serta Machiavellianisme berhubungan signifikan dengan perilaku cost-inflicting (β = 0,18, p < 0,001). Analisis mediasi menunjukkan bahwa Machiavellianisme memediasi secara parsial hubungan antara pengasuhan overprotektif ibu dan perilaku cost-inflicting (β = 0,041, p = 0,001), dengan efek total β = 0,240 (p < 0,001). Temuan ini menyoroti dampak jangka panjang pola asuh overprotektif terhadap perilaku romantis di masa dewasa dan mendorong penelitian lebih lanjut mengenai mekanisme psikologis lain yang memengaruhi strategi retensi pasangan yang manipulatif.